A neutron irradiation-induced displacement damage of indium vacancies in α-In2Se3 nanoflakes. Issue 28 (9th July 2020) - Hou, Pengfei; Wang, Xinhao; Liu, Yunxia; Chen, Yun; Dong, Shijian; Guo, Hongxia; Wang, Jinbin; Zhong, Xiangli; Ouyang, Xiaoping
Abstract : The discovery of layered two-dimensional (2D) ferroelectric materials has promoted the development of miniaturized and highly integrated ferroelectric electronics. Abstract : The discovery of layered two-dimensional (2D) ferroelectric materials has promoted the development of miniaturized and highly integrated ferroelectric electronics. The 2D ferroelectric materials can be applied in a radiation environment, in which the effect of radiation on these materials should be considered. However, the effects of radiation on 2D ferroelectric materials may be entirely different from those on traditional ferroelectric materials. Ionization effect-induced domain switching can be recovered by applying an external electric field, whereas the displacement effect initiated by radiation particles produces crystal structure damage. The displacement damage that is extremely difficult to recover may have a negative impact on the application of 2D ferroelectric materials in a radiation environment. In this study, the effect of displacement induced by neutron irradiation on the promising α-In2 Se3 nanoflakes was investigated. Neutron irradiation (1 MeV) with a fluence of 10 14 cm −2 was used for avoiding ionization effects in a certain range. Although the topography of α-In2 Se3 does not change underneutron irradiation, vacancies have been proved to be induced by neutron irradiation; furthermore, it has been identified that the vacancies mostly originate from the loss of In atoms. The out-of-plane (OOP) and in-plane (IP) domain structures of the α-In2 Se3 nanoflakes with a few layers only slighlty change. In addition, the polarization of the irradiated nanoflakes could still be reversed. All these findings show that although the vacancies may influence the band structure and polarizaiton values of α-In2 Se3, the ferroelectric performance may have a strong resistance to neutron irradiation. Therefore, our investigation implies that α-In2 Se3 is an excellent 2D ferroelectric material for application in radiation-resistant electronic devices in the future.